Book review: Nugroho, K., Carden, F. and Antlov, H. 2018: Local Knowledge Matters: Power, Context and Policymaking in Indonesia. (July 2020) - Cockburn, Jessica
Nugroho, K., Carden, F. and Antlov, H. 2018: Local Knowledge Matters: Power, Context and Policymaking in Indonesia . Bristol: Policy Press. xiii + 174 pp. £22.50 (Cloth). ISBN: 978-1447348078 (Cloth).